2016
DOI: 10.1108/jkm-05-2016-0199
|View full text |Cite
|
Sign up to set email alerts
|

Artifacts in knowledge management research: a systematic literature review and future research directions

Abstract: International audiencePurpose The purpose of this paper is to assess the role of artifacts in the knowledge management field in the past 18 years (1997-2015) and to identify directions for future research. Design/methodology/approach The authors conducted a systematic literature review of 101 articles published in seven journals retrieved from EBSCO and Google Scholar online research databases. The framework for analysis included 13 codes, i.e. author(s), title, year of publication, typology, theoretical lens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 71 publications
1
58
0
Order By: Relevance
“…Knowledge management has captured the attention of researchers in the knowledge-based economy [22], with interest in this academic and practice-oriented discipline witnessing a significant rise in recent years [23][24][25]. There is also a need nowadays to gain additional insight into how knowledge management is evolving within the context of public sector organizations [26], including social work organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge management has captured the attention of researchers in the knowledge-based economy [22], with interest in this academic and practice-oriented discipline witnessing a significant rise in recent years [23][24][25]. There is also a need nowadays to gain additional insight into how knowledge management is evolving within the context of public sector organizations [26], including social work organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Majority qualitative methodological approaches were adopted in KM research indicated by recent study by Mariano and Awazu (2016). In adopting this stance, emphasis should be placed on the aim and objectives of the research, not on formulating hypotheses.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Hence, it is argued that KM is a complex area that brings together hard, soft and abstract aspects; IT issues related to KM tools, organisational issues related to culture, as well as fundamental philosophical issues with regard to different epistemological views of knowledge. Recent findings shown lacked of cumulativeness and consistency in the current KM debate (Mariano and Awazu, 2016). This often results in the implementation of KM initiatives with either an overemphasis on technology (hard aspects) to the exclusion of adequate people management (soft aspects) or strong people management programmes hindered by inadequate enabling technologies (Moffett et al, 2003:p. 6).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the relevance of resolving this issue has been emphasized by the digitalization trend threatening to disrupt the way knowledge workers make their living (Christensen, Wang & van Bever, 2013). Indeed, a recent review article identifying four potential future directions for knowledge management research point towards specifying the knowledge process as a particularly promising future direction (Mariano & Awazu, 2016) that relates to the complex combination of three distinct phenomena: social capital, networks, and knowledge transfer (Inkpen, 1996;Inkpen & Tsang, 2005;. This paper relates directly to this discourse in that it aims to explain how specific communication roles are instrumental in capturing knowledge value creation and its subsequent monetization.…”
Section: Introductionmentioning
confidence: 99%